Disruption of Nucleotide Homeostasis by the Antiproliferative Drug 5-Aminoimidazole-4-carboxamide-1-β-d-ribofuranoside Monophosphate (AICAR) - Ceschin, Johanna (J Biol Chem, 2015)
5-Aminoimidazole-4-carboxamide-1-β-d-ribofuranoside monophosphate (AICAR) is a natural metabolite with potent anti-proliferative and low energy mimetic properties. At high concentration, AICAR is toxic for yeast and mammalian cells, but the molecular basis of this toxicity is poorly understood. Here, we report the identification of yeast purine salvage pathway mutants that are synthetically lethal with AICAR accumulation. Genetic suppression revealed that this synthetic lethality is in part due to low expression of adenine phosphoribosyl transferase under high AICAR conditions. In addition, metabolite profiling points to the AICAR/NTP balance as crucial for optimal utilization of glucose as a carbon source. Indeed, we found that AICAR toxicity in yeast and human cells is alleviated when glucose is replaced by an alternative carbon source. Together, our metabolic analyses unveil the AICAR/NTP balance as a major factor of AICAR antiproliferative effects.